Rescue bare-metal stent placement restoring multilevel perfusion in acute type B aortic dissection: a case report - Nakamura, Ken; Arai, Shusuke; Kim, Cholsu; Uchino, Hideaki (Frontiers in Cardiovascular Medicine, 2026)
We report a rare, life-saving endovascular intervention in a patient with acute type B aortic dissection (TBAD) complicated by severe lower limb ischemia due to dynamic obstruction. A 67-year-old woman, previously diagnosed with uncomplicated Stanford type B dissection with a thrombosed false lumen, suddenly developed bilateral leg pain and absent distal pulses on day 12. CT revealed a new entry tear in the descending aorta, leading to false lumen reperfusion and collapse of the true lumen at the abdominal aorta and both common iliac arteries. As appropriate thoracic endovascular aortic repair and endovascular aortic repair devices were not immediately available, emergency repair was performed using four self-expanding bare-metal stents via bilateral femoral access. This achieved prompt true lumen re-expansion and restoration of distal pulses. Post-procedure imaging confirmed improved perfusion. Although extra-anatomical bypass is often considered, complete collapse of the abdominal true lumen made it unlikely to be effective. This case demonstrates that widely available bare-metal stents offer a practical and effective emergency option for restoring distal perfusion when standard devices are not accessible. Importantly, this approach should be regarded as palliative for limb salvage rather than definitive treatment of the entry tear.